Integration of the Digital broadcast MObile television NETwork and the 3G network - Šunjevarić, Milan Manojle; Popović, Milorad L.; Todorović, Branislav M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The paper presents results of research of the possibility for the integration of mobile broadcast TV networks and cellular 3G networks. We analyzed trends in mobile television services based on the previous studies that aim to find optimal ways to integrate different types of networks. This paper analyzes the existing technology for mobile television, with special emphasis to the DVB-H technology. We analyzethe conditions, reasons and opportunities for the integration of DVB-H and 3G UMTS (Universal Mobile Telecommunications System), and the conclusions of these analyzes are supported with the results of practical work. Based on these studies we conclude on the feasibility of realization DVB-H/UMTS hybrid networks.